2017
DOI: 10.1371/journal.pone.0178685
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms associated with fatty liver disease and fibrosis in HIV positive patients receiving combined antiretroviral therapy (cART)

Abstract: Hepatic steatosis can occur with any antiretroviral therapy (cART). Although single nucleotide polymorphisms (SNPs) have been identified to predispose to alcoholic and non-alcoholic fatty liver disease, their role for treatment-associated steatosis in HIV-positive patients remains unclear. We determined the frequency of PNPLA3 (rs738409), CSPG3/NCAN (rs2228603), GCKR (rs780094), PPP1R3B (rs4240624), TM6SF (rs8542926), LYPLAL1 (rs12137855) and MBOAT7 (rs626283) by RT-PCR in 117 HIV-positive patients on cART and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In conclusion, the rs641738 is not associated with NAFLD in our population. The association of the variant and NAFLD as disease trait could not be replicated in population-based or hospital based studies from Asia 16 – 18 , 20 or Germany 14 . Nevertheless, the association with liver histology, including fibrosis was only observed in patients with NAFLD of European ancestry 12 14 ; this finding could not be replicated in studies that included Asian population 16 , 17 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In conclusion, the rs641738 is not associated with NAFLD in our population. The association of the variant and NAFLD as disease trait could not be replicated in population-based or hospital based studies from Asia 16 – 18 , 20 or Germany 14 . Nevertheless, the association with liver histology, including fibrosis was only observed in patients with NAFLD of European ancestry 12 14 ; this finding could not be replicated in studies that included Asian population 16 , 17 .…”
Section: Discussionmentioning
confidence: 91%
“…Meanwhile this manuscript was under the peer review process, several reports on the role of rs641738 were published 16 – 18 , 20 ; specifically, there were large studies that included well characterized patients diagnosed by liver biopsy 16 , 17 . Interestingly, these studies showed a negative association of the variant with NAFLD 16 – 18 , 20 and NASH or liver fibrosis 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there are limited studies that have characterized the distribution and associations of PNPLA3 polymorphisms in those with HIV in the U.S. population which is ethnically and racially different from studies in European populations. 12,13 Second, some investigators have speculated that disease progression and injury would be greater in those with risk for NASH combined with HCV infection. Indeed, a recent meta-analysis suggested that the GG allele was highly associated with the risk of advanced liver fibrosis and steatosis in Caucasian populations with chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…At last, the remaining 17 case-control studies were qualified for our meta-analysis (Fig. 1) [8, 13, 14, 20–32].
Fig.
…”
Section: Materias and Methodsmentioning
confidence: 99%